Peningkatan Hasil Belajar Matematika Menggunakan Pendekatan Contextual Teaching And Learning Pada Materi Bangun Datar Segi Empat - Rahmawati, Nurina Kurniasari; Kusuma, Arie Purwa (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2020)
This study aims to improve student activity and student mathematics learning outcomes through the Contextual Teaching And Learning learning method for VII grade students of AR Rahmah Ujung Krawang, East Jakarta 2019/2020. This research is a classroom action research. The research subjects are Grade VII students of AR Rahmah Ujung Krawang, totaling 30 students. Data collection techniques were taken using observations, field notes, documentation, and tests. Analysis of the data from this study was descriptive qualitative, namely by analyzing student development data from cycle I to cycle III. The results showed that an increase in student activity can be seen from the increase in student activity in the first cycle by 56.25%, in the second cycle 68.75% and in the third cycle reached 8.38%. While the improvement in student learning outcomes can be seen from working on exercises with the achievement of KKM scores, before action 41.66%, in the first cycle obtained an average of 69.33 with a percentage of 53.33%, the second cycle obtained an average of 76 with a percentage of 70, 00%, and the third cycle obtained an average of 80 with a percentage of 86.67%. The conclusion of this study is that through the Contextual Teaching And Learning learning method obtained mathematics learning outcomes of VII grade students of AR Rahmah Ujung Krawang, East Jakarta.